2021
DOI: 10.4055/cios20058
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of and Risk Factors for Hypovitaminosis D in Patients with Rotator Cuff Tears

Abstract: Vitamin D deficiency is known to affect more than 1 billion people worldwide. 1) In the USA, its prevalence has been reported to be 40%. 2) Recently, vitamin D deficiency in Asian countries has been the focus of attention because it has been reported to have a prevalence of up to 70%. Vitamin D deficiency in Asian countries seems to be more serious than that in western countries. 3,4) Based on the Korea National Health and Nutrition Examination Survey (KNHANES), there has been a gradual increase in the prevale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…Various studies have been performed on the role of vitamin D in rotor cuff repair, and studies have shown a reduction in vitamin D and the risk of rupture of the rotator cuff (21,22), although other studies have rejected these results (23). One of the limitations of this study was the small number of patients based on inclusion criteria, due to need to eliminate study confounders and that only symptomatic patients with a history of shoulder pain were included in the study.…”
Section: Discussionmentioning
confidence: 94%
“…Various studies have been performed on the role of vitamin D in rotor cuff repair, and studies have shown a reduction in vitamin D and the risk of rupture of the rotator cuff (21,22), although other studies have rejected these results (23). One of the limitations of this study was the small number of patients based on inclusion criteria, due to need to eliminate study confounders and that only symptomatic patients with a history of shoulder pain were included in the study.…”
Section: Discussionmentioning
confidence: 94%
“…Lee et al (2021) [ 72 ] conducted a retrospective study on a large group of people who had undergone rotator cuff repair. The concentration of 25(OH)D was measured in patients at the time of qualification for surgical treatment of the injury.…”
Section: Resultsmentioning
confidence: 99%
“…Vitamin D deficiency can lead to low BMD and an increased risk of falls and OVCF [ 13 , 14 ]. Although the effect of vitamin D supplementation on the rate of OVCF has been investigated in studies [ 15 ], no study has investigated the effects of vitamin D supplementation after the onset of OVCF.…”
Section: Discussionmentioning
confidence: 99%